2010
DOI: 10.1080/15226510903390411
|View full text |Cite
|
Sign up to set email alerts
|

Phytostabilisation of Copper-Contaminated Soil in Katanga: An Experiment with Three Native Grasses and Two Amendments

Abstract: This study evaluates the feasibility of using the grass species Rendlia altera, Monocymbium ceresiiforme, Cynodon dactylon, and amendments (compost and lime) for the phytostabilisation of soils contaminated by Cu in the province of Katanga (Democratic Republic of Congo). Species were grown on control and Cu-contaminated plots (artificially contaminated with 2,500 mg kg(-1) Cu) unamended (NA), amended with 4.5 kg compost m(-2) or 0.2 kg lime m(-2). R. altera was also grown on contaminated plots amended with 22.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 30 publications
0
33
0
3
Order By: Relevance
“…To assess human exposure to pollution in Katanga, which is a real public health concern due to the high population density in the contaminated area, Banza et al (2009) measured metal concentrations in urine of people living close to mines or smelting plants. Concentrations of Co and other metals were higher in the urine of people living close to mines or smelting plants (including the site contaminated by the Cu-smelter industry of Lubumbashi), exceeding the baseline value of the Centers for Disease Control and Prevention (Shutcha et al, 2010).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…To assess human exposure to pollution in Katanga, which is a real public health concern due to the high population density in the contaminated area, Banza et al (2009) measured metal concentrations in urine of people living close to mines or smelting plants. Concentrations of Co and other metals were higher in the urine of people living close to mines or smelting plants (including the site contaminated by the Cu-smelter industry of Lubumbashi), exceeding the baseline value of the Centers for Disease Control and Prevention (Shutcha et al, 2010).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…In an experimental garden study performed on soil artificially contaminated with copper sulphate, Shutcha et al (2010) showed toothbrush grass was a promising species for phytostabilisation. The present study extended these results to in situ conditions; and to our knowledge was the first successful field phytostabilisation trial of trace metal polluted soil in tropical Africa.…”
Section: Successful Establishment Of M Altera On Bare Soilmentioning
confidence: 99%
“…Under experimental garden conditions, on soil artificially contaminated by Cu with Cu sulphate, the adaptive trait of Cu tolerance in some species from secondary metalliferous habitats were examined. Shutcha et al (2010) demonstrated Toothbrush grass (M. altera (Rendle) Stapf) is high Cu tolerant species and exhibited high potential for phytostabilisation on soils artificially treated with copper sulphate on a field experiment.…”
Section: Introductionmentioning
confidence: 99%
“…It was followed by A. xanthophloea while G. robusta showed poor performance and recorded the lowest growth increments. In the province of Katanga, D.R Congo, the feasibility of using three grass species (Rendlia altera (Rendle) Chiov, Monocymbium ceresiiforme (Nees) Stapf, C. dactylon (L.) Pers), and two soil amendments (compost and lime) for the phytostabilization of soils contaminated by Cu was evaluated (Shutcha et al 2010). Results demonstrated high survival of R. altera on un-amended soil, suggesting that this species is a good candidate for phytostabilization, while liming ensured survival of C. dactylon and increased plant reproduction and reduced copper accumulation in leaves compared to compost.…”
Section: Restoration Research and Practice In Africamentioning
confidence: 99%